2004
DOI: 10.3748/wjg.v10.i15.2205
|View full text |Cite
|
Sign up to set email alerts
|

Honokiol induces apoptosis through p53-independent pathway in human colorectal cell line RKO

Abstract: Honokiol can induce RKO cells apoptosis through activating caspase cascade by p53-indepenent pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
84
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(91 citation statements)
references
References 21 publications
7
84
0
Order By: Relevance
“…Growth inhibition was observed in all breast cancer cell lines tested, regardless of their HR, HER2 or p53 status, but it was not observed for glioblastoma multiforme cells. Similar to other tumors (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), our studies revealed LC50 at a range of 29-50 μM for breast cancer cell lines. Of interest, the lowest LC50 values were observed for the HR-negative, p53-mutated MDA-MB-231 and SK-BR-3 cell lines.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Growth inhibition was observed in all breast cancer cell lines tested, regardless of their HR, HER2 or p53 status, but it was not observed for glioblastoma multiforme cells. Similar to other tumors (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), our studies revealed LC50 at a range of 29-50 μM for breast cancer cell lines. Of interest, the lowest LC50 values were observed for the HR-negative, p53-mutated MDA-MB-231 and SK-BR-3 cell lines.…”
Section: Discussionsupporting
confidence: 56%
“…HNK stimulated cleavage of PARP and upregulation of expression of BAX, but did not affect levels of BAD or Bcl-2. Upregulation of BAX was also observed in B-CLL following HNK treatment, while upregulation of Bad was observed in colon and lung cancers (10,11,14,15). Thus, HNK may be involved in the activation of different members of the Bcl-2 family in different tumors.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This is consistent with other studies showing that M. officinalis extract treatment induces cell growth inhibition in several cell lines (24,25,35). The inhibition was due to cell cycle arrest in G1 phase.…”
Section: Discussionsupporting
confidence: 82%
“…Previous reports have demonstrated that honokiol induces cell apoptosis in several cell lines, such as leukemia cell lines HL-60, colon cancer cell lines RKO, lung cancer cell lines A549 and CH27. [9][10][11][12][13][14] It also has remarkable in vivo antitumor activities in tumor mouse models. 15 Honokiol has demonstrated potent antiangiogenic and antitumor properties against aggressive angiosarcoma by blocking of VEGF-induced VEGF receptor 2 autophosphorylation.…”
mentioning
confidence: 99%